Cloud point preconcentration of gold (III) and determination by flame atomic absorption spectrometry - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2013)
A simple and sensitive method has been developed for trace gold (III) extraction by cloud point extraction preconcentration and detection with flame atomic absorption spectrometry. In this study sulphathiazolylazo resorsin and Triton X-100 are used as a complexing agent and surfactant respectively. The cloud point is formed in the presence of Triton X-100 plus phenol at room temperature. The optimal extraction and reaction conditions such as pH, amount of reagents, equilibration temperature time and the effect of diverse ions are studied. Under the optimized experimental conditions, the detection limit of 0.75 mu g/L-1 along with enrichment factor of 31 for gold (III) are achieved. The procedure has been applied to the determination of gold in water and ore samples
Keywords: Cloud-point extraction; Flame atomic absorption spectrometry; Gold; Sulphathiazolylazo resorsin; Triton X-100; WATER SAMPLES; SELECTIVE DETERMINATION; NONIONIC SURFACTANT; EXTRACTION; GOLD(III); COPPER; SEPARATION; PALLADIUM